A study on the customers’ intention to use self-vollection service for lastmile delivery on international retail business in Malaysia - Lam, Sim Jean (2022)
The main objective of conducting this research project is to examine the customer engagement behavior in using self-collection services for last-mile delivery on international retail stores in Malaysia in co-creating the value of logistics service. Innovation diffusion theory (IDT) and added perceived trust have been tested and examined in this research. Thus, various factors were examined such as trialability, complexity, relative advantage, compatibility, observability and perceived trust will bring an impact on the customers' intention to use self-collection services. A quantitative method approach is used and 250 survey questionnaires are distributed to Malaysians by using convenient sampling technique but only 245 survey questionnaires are qualified as 5 respondents failed to fulfil the research’s requirements All the surveys are soft copies which distribute online. The data collected from the survey questionnaire can be analysed using the Statistical Package for Social Science (SPSS). The results obtained from SPSS indicate that all independent variables have a significant relationship with the dependent variable. The research also discussed the limitations encountered during the research project's progress and provided recommendations for future researchers.